Sistema para el análisis del comportamiento térmico y monitoreo mediante el uso de un algoritmo en el invernadero N°2 de la Universidad Técnica de Cotopaxi Campus Salache. - Tapia Villamarin, Antonio Agustin (2020)
In the career of Electrical Engineering, new proposals have been developed for the benefit of the teaching and learning of the students of the institution. That is why the monitoring of maximum temperatures inside the greenhouse is added to the andean grain department for the Salache Campus greenhouse N° 2. The system is made up of an impermeable temperature sensor and two fans located according to the specific calculations for its sizing, which allow an adequate air flow inside the greenhouse, considerably reducing the high temperatures that can be harmful during the germination process of each crop. The maximum and minimum temperature ranges allowed are in the HMI, so if the temperature exceeds the maximum allowed, it will activate the fans, considerably lowering the temperature inside the greenhouse. Through the combination of an electrical and electronic system which allows monitoring the variable of interest mentioned in a precise way according to the behavior that can be presented during the collection of data from the sensor located at the top of the greenhouse, facilitating the user the monitoring and control of the system through an HMI interface in the WINCC software, thanks to the real measurements stored in the database of the web server and web platform. Allowing teachers, students or authorized personnel to obtain information and manual or automatic control of the whole system thanks to a man-machine interface in a didactic way and easy handling by people through the WINCC software.